Kesehatan Mental Mahasiswa dalam Perspektif Sosiologi: Analisis Tekanan Sosial dan Akademik - Faris Rabbani; Achmad Hufad; Yani Achdiani (Jurnal Ilmu Sosial dan Humaniora, 2026)
Student mental health has become an increasingly significant issue within the context of higher education. This article aims to examine student mental health from a sociological perspective by highlighting the influence of social and academic pressures. The study employs a qualitative approach through a literature review of relevant sources. The findings indicate that academic pressures, such as heavy workloads, achievement demands, and competition, contribute to the emergence of stress among students. In addition, social pressures, including family expectations, peer dynamics, and socially constructed notions of success, also affect students’ mental conditions. From a sociological perspective, this issue is understood as the result of interactions between individuals and social structures that shape norms and expectations. Therefore, support from educational institutions and the broader social environment is needed to create more conducive conditions for maintaining student mental health.